Application of sandwich-based PBL teaching on the medical immunology workshop - He, Cairong; Cheng, Yuyang; Zheng, Fang; Lei, Ping (Frontiers in Education, 2026)
IntroductionThe Medical Immunology course is a basic and continuously updating medical course for medical students. As this course involves complex concepts, students are often frustrated by the amount of detailed material and find it hard to link the various knowledge points exactly and entirely. More effective and more engaging pedagogy beyond traditional didactic approaches is needed to drive students’ attention, understanding and memorizing more knowledge of medical immunology.MethodsIn this article, we illustrate how Sandwich-based PBL approach is applied in a 4-class workshop to this course and how to assess its advantages by examination scores and questionnaire.ResultsThis Sandwich-based PBL approach could significantly improve students’ self-learning and critical thinking capabilities, communication skills and learning interests.DiscussionWe need to make great efforts to maximize the advantages of the approach and to extend this approach to more departments or more basic courses.